THE EUROPEAN UNION’S AVIATION SECURITY POLICY EVOLUTION AND ITS IMPLICATIONS TO INDONESIA - Hartono, Stephanie Putri (Veritas et Justitia, 2024)
Advances in aviation transportation have increased threats to security, prompting the European Union (EU) to take decisive actions. This research examines the evolution of the EU’s aviation security laws and their implications for Indonesia. Using a normative legal research approach, the study finds that EU aviation security measures have been significantly influenced by external and internal factors. Key developments include the integration of aviation security post-9/11 with Regulation (EC) No. 2320/2002, its replacement by Regulation (EC) No. 300/2008, the near-ban on liquids after the 2006 Trans-Atlantis liquid bomb plot, the installation of security scanners following the 2009 underwear bomb plot, and the ACC3 system post-2010 Yemen incident that revoked Regulation (UE) No. 185/2010. Cyber threats are also a growing concern. This research is important as these EU measures impact Indonesia’s national aviation security standards.